Strategic Energy Management in Energy intensive enterprises: SWOT-AHP analysis of Indian recycled Paper and Pulp Industry - Anand Narhari Sonsale, Yashpal Kaushik, S. D. Pohekar, Jayant Purohit (International Journal of Modern Agriculture, 2021)
For energy intensive industries, such as Paper and Pulp industry, energy costs form a significant part of the overall costs and hence economizing on energy isone of the targets towards enhancing profits. One important aspect of strategic energy management is to improve energy efficiency (EE) of the plant. Out of the multiple factors that affect the energy performance of a plant, the managements can concentrate on select few only on account of limitation of resources. Such a prioritization has been attempted in this work, using a hybrid method combining strengths, weaknesses, opportunities and threats (SWOT) analysis with Analytic hierarchy process (AHP). This has been applied to Indian recycled Paper and Pulp Industry. Sixteen factors that influence implementation of energy efficiency measures (EEMs) were identified and then prioritized quantitatively based on industry expert’sopinion. The analysis brings out that the industry values profitability the most. High energy cost, competition, management support and capital availability emerge as the top four factors. It is also seen that environmental policies and sectoral policies for paper and pulp industry, even though mandatory, do not influence the implementation of EEMs in a significant way. Community pressure, emerging technologies, renewable energy, production inefficiencies, qualified human resource are other factors identified. Sourcing of energy, scarcity of coal and waste paper collection deal with important factors of paper production but the experts have prioritized them lower down in the list. In comparison of the overall SWOT groups, external threats emerge to be the most important SWOT group followed by internal strengths.The work provides an insight into factors that influence EE in recycled paper and pulp industry.